Bird Use of Bobwhite Brush Shelters on a Conservation Reserve Program Field - Louis A. Harveson; Nick I. Kassinis; Fred S. Guthery (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) are known to use constructed brush shelters. The establishment of artificial shelters is a common practice in grasslands where woody cover is lacking. We evaluated the use of brush shelters by bobwhite and other bird species in a Conservation Reserve Program (CRP) field. Twenty-seven species of birds were observed at brush shelters versus 10 species at control sites. No species occurred exclusively at control sites. Brush shelters in CRP had positive effects on avian communities by providing sites for vocalizing, prey search, loafing, and nesting.